Perception of Lemborexant Effectiveness as Assessed by the Patient Global Impression–Insomnia Questionnaire - Drake, Christopher; Yardley, Jane; Pinner, Kate; Moline, Margaret; Malhotra, Manoj (Nature and science of sleep, 2025)
Using data from a clinical study of lemborexant, evaluate responses to the Patient Global Impression-Insomnia (PGI-I) questionnaire, a simple 4-item questionnaire that assesses patients' perceptions of the effects of medication on sleep, which may help evaluate clinically meaningful changes from the patient's perspective. Study E2006-G001-303, a 12-month, placebo (PBO)-controlled (first 6 months) Phase 3 study in adults with insomnia disorder, randomized subjects (1:1:1) to lemborexant 5 mg (LEM5; n=316), 10 mg (LEM10; n=315), or PBO (n=318). The second 6 months are not presented here. PGI-I results were analyzed post hoc in relation to patient-reported (subjective) sleep-onset latency (sSOL) and total-sleep-time (sTST). At 6 months: 67.3% (LEM5) and 68.8% (LEM10) of subjects reported positive effects of medication helping them sleep versus 45.0% (both <0.0001) with PBO. Positive effects on "time to fall asleep" were reported by 72.8% (LEM5) and 73.1% (LEM10) versus 46.1% with PBO ( <0.0001), and 58.0% (LEM5) and 62.0% (LEM10) reported positive effects on sleep duration versus 39.9% with PBO ( <0.0001). Subjects reporting positive effects on "time to fall asleep" had greater change from baseline (CFB; improvement) at 6 months in median sSOL (in minutes; LEM5= -26.8; LEM10= -32.1; PBO= -17.5; <0.01) versus those reporting negative effects (LEM5= -9.1; LEM10= -10.4; PBO= -8.6; LEM5 vs PBO, =0.52; LEM10 vs PBO, =0.69). For sTST (in minutes) at 6 months, mean CFB tended to be greater for subjects reporting positive (LEM5=81.2, LEM10=93.2, PBO=74.8; LEM5 vs PBO, =0.28; LEM10 vs PBO, =0.18) versus negative (LEM5=46.4, LEM10=35.0, PBO=38.6; LEM5 vs PBO, =0.44; LEM10 vs PBO, =0.52) effects, although this was not statistically significant. Patient impressions of the effects of lemborexant were positive based on the PGI-I and reflected improvements in subjective sleep outcome measures, indicating that the brief PGI-I tool may be useful in clinical practice.